Segmenting International Tourists in Indonesia: A Cluster Analysis of Preferences, Motivations, and Behaviors - Wang, Tz-Li; Azizurrohman, Muhammad (Journal of Economics Research and Social Sciences, 2025)
This study conducts a cluster analysis of international tourists visiting Indonesia to identify distinct market segments based on travel motivations and behaviors. A sample of 1,050 respondents revealed four key segments: Leisure Seekers, Cultural Explorers, Adventure Enthusiasts, and Budget Travelers. Leisure Seekers from Australia and Germany are drawn to luxury and wellness experiences. At the same time, Cultural Explorers, mainly from China and Japan, are motivated by cultural heritage. Adventure Enthusiasts, younger tourists from Europe and the United States, prefer outdoor activities and eco-friendly tourism, whereas Budget Travelers prioritize affordability. The study emphasizes the importance of tailored marketing strategies to meet the needs of these diverse segments. The discriminant and silhouette analysis validated the clusters, confirming their statistical significance. These findings provide actionable insights for tourism operators and policymakers in Indonesia, offering a roadmap for enhancing visitor satisfaction and promoting sustainable tourism development. Despite its contributions, the study is limited by its focus on major destinations and a defined period, which may not capture evolving tourism trends. Future research should explore niche markets, track changes over time, and assess the effectiveness of targeted marketing strategies. This research highlights the need for segmentation in tourism marketing to sustain Indonesia’s competitiveness in the global market.